HUBUNGAN KADAR ZAT BESI SERUM DENGAN KONSENTRASI ZAT BESI ASI IBU MENYUSUI DI KABUPATEN SELUMA - Ariana, Rika; Flora, Rostika; Sitorus, Rico Januar; Zulkarnain, Mohammad; Hasyim, Hamzah; Fajar, Nur Alam; Ermi, Nurmalia; Jasmine, Annisah Biancika; Aguscik, Aguscik; Ikhsan, Ikhsan; Slamet, Samwilson; Purnama, Yetti; Sulung, Neshy (Mitra Raflesia (Journal of Health Science), 2023)
Background: Maternal iron status affects infant neurocognitive development. When the maternal iron intake and status are disturbed, it can lead to iron deficiency which can lead to anemia if not treated.  Anemia in breastfeeding mothers has a negative impact on the quality and volume of breast milk, including the availability of iron in breast milk. This study aims to analyze the relationship between serum iron levels and breast milk iron concentration in breastfeeding mothers in Seluma Regency. Methods: This study was an analytic survey, cross-sectional design, conducted in Seluma Regency in 4 (four) public health center working areas, namely Rimbo Kedui Public Health Center, Talang Tinggi, Tais, and Masmambang. Respondents were 124 breastfeeding mothers of children aged 0-24 months who were taken by proportional consecutive sampling. Venous blood and breast milk samples were collected for iron level measurement. Iron measurement was done using the spectrophotometric method. Data on characteristics were obtained using a questionnaire. Furthermore, the data were analyzed univariately and bivariately. Results: The results of measuring iron levels showed that 38.7% of mothers had iron deficiency and 15.3% of mothers had low breast milk iron levels. The bivariate test results showed 25% of mothers who experienced iron deficiency had low breast milk iron levels. (p=0.034, OR= 3.28; CI= 1.190-9.071). Conclusion: There is a significant relationship between serum iron levels and breast milk iron levels in breastfeeding mothers. It is necessary to educate mothers regarding the prevention of iron deficiency during pregnancy and breastfeeding so that the quantity of breast milk iron can meet the needs of children during breastfeedingKeyword : Breast milk, Iron Deficiency, Breast milk Iron Level, Iron